2004
DOI: 10.1002/jca.20006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different LDL‐apheresis methods on parameters involved in atherosclerosis

Abstract: LDL-apheresis lowers the LDL level in patients with severe hypercholesterolemia. The present study compared three apheresis methods--DSA, DALI, and plasma exchange--for effectiveness in removal of LDL and effect on various blood parameters involved in atherogenesis. The study group included 6 patients with primary hypercholesterolemia unresponsive to maximal drug therapy. All were treated first with 4 consecutive plasma exchange sessions followed by 4 DSA sessions; in four out of six, an additional 4 sessions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 21 publications
(19 reference statements)
1
10
1
Order By: Relevance
“…Hershcovici et al systematically compared plasmapheresis, dextran sulfate attached cellulose (DSA), and the whole blood DALI system in four patients and found a 47.5%, 36.1%, and 22% reduction in hs-CRP, respectively [14]. We found the largest reduction in hs-CRP for the whole blood column DL-75.…”
Section: Hs-crpmentioning
confidence: 66%
“…Hershcovici et al systematically compared plasmapheresis, dextran sulfate attached cellulose (DSA), and the whole blood DALI system in four patients and found a 47.5%, 36.1%, and 22% reduction in hs-CRP, respectively [14]. We found the largest reduction in hs-CRP for the whole blood column DL-75.…”
Section: Hs-crpmentioning
confidence: 66%
“…As atherosclerosis is a systemic inflammatory disease, it may be of interest to know whether there is a difference between the various methods in their effects on inflammatory and other surrogate markers that may have a role in the pathogenesis of atherosclerosis. Although we and others [13,23] reported some differences between various methods, the clinical significance is yet unproven. Blockade of the renin-angiotensin system is needed in many patients, and if DSA or DALI apheresis are used, then it should be done only by angiotensin receptor blockers because administration of angiotensin converting enzyme inhibitors is associated with untoward effects due to disturbances in the bradykinin pathway [24,25].…”
Section: Discussionmentioning
confidence: 76%
“…They also found a significant increase in leukocytes for DSA and plasmapheresis, but a reduction for the DALI system [25]. Kopprasch et al have previously shown an increase in the leukocyte count and in the leukocyte burst activity with the heparin-induced extracorporeal LDL precipitation (HELP) system, but no alteration in the leukocyte count with the whole blood DALI system, whereas the leukocyte burst activity decreased [26].…”
Section: Hematological Parametersmentioning
confidence: 92%
“…Hershcovici and coworkers compared plasma exchange with dextran sulfate-cellulose adsorption (DSA) and direct adsorption of lipoprotein (DALI) from whole blood and found a significant decrease in hemoglobin for DALI and DSA, but not so for plasma exchange [25]. We observed a significant decrease in hemoglobin with the whole blood column DL-75 in accordance with Hershcovici's findings for the DALI system, however we found an increase in hemoglobin for both the plasma columns (LA-15 and EC-50W), contrary to the decrease noted with the DSA column used by Hershcovici et al (Liposorber, LA-40, Kaneka Corporation, Japan).…”
Section: Hematological Parametersmentioning
confidence: 97%